UV-assisted tumble washing and chilled storage of shucked mussel meat - Nobleza, Maricel Marcelo; Azanza, Ma. Patricia V. (2007.)
ABSTRACT This study established the shelf life of mussel meats subjected to heat shocking and combination treatment of heat shocking and UV-assisted chilled tumble washing that were stored at refrigerated conditions (5± 1°C) in polyethylene (PE) tubs and half-shells on polystyrene (PS) trays for a period of 2 wk. Shellstock meats exposed only to heat shocking that were packed in the two test packaging materials established a maximum refrigerated shelf life of 7d while those exposed to the combination treatments and packed in half-shells on trays established a maximum shelf life of up to 10 d for the meats packed in half-shells on trays. It was also established that meats packed in half-shells on trays have better microbial and sensory qualities at the end of 2 wk chilled storage period relative to those meats packed in tubs. The meats in half-shells on trays were considered to be exposed to lesser mechanical damage resulting to meat compression and deformation and, liquor extraction than those meats packed in tubs. Microbial and sensory qualities of both the test processed shellstock forms established in this study were considered as better determinants of the mussel meat shelf life than the established physical qualities. This study recommended the application of the combination treatments of heat shocking and UV-assisted tumble washing as a value-adding protocol to extend the shelf-life of the green mussel meat. Likewise, this study recommended that green mussek meats that were exposed to heat shocking and UV-assisted tumble washing are better stored in half-shells on trays than in tubs stored at chilled condition (5 ± 1°C) to achieve an extended shelf life of 10 d. This study was conducted as part of the project entitled Application of Ozone-, Ultraviolet- and Chlorine-Assisted Chilled Water Treatments for Heat Shucked Philippine Green Mussels funded by the Bureau of Fisheries and Aquatic Resources, Department of Agriculture implemented by the College of Home Economics, University of the Philippines, Diliman Quezon City with Dr. Maria Patricia V. Azanza as project lead
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Mussels -- Preservation; Mussels -- Microbiology